Semiotical Narrative of the Greimai Bridge in Prienai - Smolskaitė, Giedrė (Semiotika, 2019)
In 2017, the world celebrated 100 years since the birth of Algirdas Julien Greimas (1917–1992). The anniversary inspired many commemorative works, events, conferences, research projects, etc. That is also the case with this paper. Here, instruments of semiotic analysis are applied to a rather unusual object – a bridge located in the town of Prienai, Lithuania. In 2010, the bridge was given the name of Greimai by the Government of Lithuania as a way of paying tribute to Julius Greimas (1882–1942), schoolteacher and burgomaster of Prienai (1934–40), and his son Algirdas Julien Greimas, literary scientist and semiotician who as a child liked to wander the woods of Prienai. The paper discusses the semantics and narrativity of the Greimai bridge. The main focus is on its function, the characteristics of the bridge and its shores, the semantic universe it embodies. Also considered is the transformation from a simple and concrete structure with a clearly defined function to a symbolic monument. The findings of this small research suggest that the bridge’s characteristics make the Greimai name a good fit and that it creates additional meanings: one recognizes plurality and duality, the echo of the father-son relationship, cyclicality and rituality, etc. In addition, the bridge appears to act as a mediator between nature and culture, life and death.